The Girl Crusoes: A Story of the South Seas - Strang, Herbert; Tenison, N. (Nell Marion), 1867-1953 (Salt Lake City, UT : Project Gutenberg, 2011)
"The Girl Crusoes: A Story of the South Seas" by Mrs. Herbert Strang is a fictional novel written in the early 20th century. The story follows three sisters$1 (BTommy, Elizabeth, and Mary$1 (Bwho, after surviving a shipwreck, find themselves stranded on a mysterious island in the South Seas. The narrative promises adventure, exploring themes of resilience and sisterly bonds as the girls navigate their new life while hoping for rescue and facing the unknown. At the start of the tale, the sisters are introduced through a series of events leading to their uncle's arrival. The excitement of his impending return is tangible, but the situation quickly escalates into adventure when their ship faces a catastrophic storm that leads to disaster. Following their escape in a dinghy, they land on an uncharted island, filled with lush vegetation and uncertainty. The opening chapters set the stage for the girls' journey of self-discovery and survival as they grapple with their circumstances, showcasing their different personalities while igniting a spirit of adventure and resolve amidst daunting challenges. (This is an automatically generated summary.)s
Release date is 2011-11-01
Produced by Al Haines
Keywords: Shipwreck survival -- Juvenile fiction; Islands -- Juvenile fiction; Adventure stories; Girls -- Juvenile fiction; Uncles -- Juvenile fiction; Shipwrecks -- Juvenile fiction; Sisters -- Juvenile fiction; South Pacific Ocean -- Juvenile fiction